Add-On Cases in the Endoscopy Unit: Factors That Affect Volume. (2009) - Segal, B; Lam, E; Amar, J; Bressler, B; Halparin, L; Ramji, A; Telford, J; Whittaker, S; Enns, R
Abstract : BACKGROUND: Although most procedures in the endoscopy clinic are elective, emergency add-on cases in hospital-based endoscopy clinics are common, frequently consuming a great deal of time and resources relative to elective endoscopy procedures. OBJECTIVE: To determine which specific factors correlate with the high volume of add-on emergency cases in a tertiary care, hospital-based endoscopy unit. METHODS: A retrospective chart review of all gastrointestinal add-on, and electively booked cases of esophagastroduodenoscopy (EGD), colonoscopy (C) and flexible sigmoidoscopy (FS) procedures from September 2006, to May 2007 was conducted. The day of the week, month, type of procedure and physician were recorded. Emergency add-on procedures performed during the weekends were not assessed. These cases were then compared with elective cases during a similar time frame to determine differences in the aspects of add-on cases versus those that were elective. RESULTS: Seven hundred twenty-one add-on cases were reviewed (mean patient age 57.4 years; 46% women) and compared with 736 elective cases (mean age 56 years; 49% women; P not significant). Of the add-on cases, 377 (52%) were EGD, 216 C (30%) and 105 (15%) were FS, with 23 combined procedures (3.2%) versus 202 (27%) EGD, 442 (60%) C and 74 (10%) FS in the elective group. Add-on cases were more likely to be EGDs than elective cases (OR 2.7; 95% CI 1.8 to 4.3; P<0.0001) and less likely to be Cs (OR 0.24; 95% CI 0.15 to 0.38; P<0.0001). There were significantly more add-on cases on Mondays (OR 1.7; 95% CI 1.0 to 2.28; P>0.03). Conversely, there were significantly fewer procedures added on Fridays (OR 0.31; 95% CI 0.16 to 0.57; P=0.0001). There were statistically fewer add-on cases in September compared with the other months that were evaluated (OR 0.31; 95% CI 0.11 to 0.78; P=0.0006). Conclusion: With the present system of performing only emergency cases on the weekend, Monday tends to have more add-on cases. Consistent with the fact that upper gastrointestinal bleeding is the most common emergency condition, EGD is more common in add-on cases than with elective cases. Although speculative, the reasons for Friday having fewer add-on cases may be the result of a change of physician on call that day; consequently, most cases may be performed earlier in the week. For unknown reasons, fewer cases tend to be added on in September than in the other months evaluated. These data demonstrate that even in the same institution with similar patients, variability in the number of add-on cases likely is a result of many additional factors governing add-on cases, which require appropriate resource planning to ensure adequate allocation of services to ensure ideal patient care.